2023
DOI: 10.1097/md.0000000000033621
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes of ectopic pregnancy with conservative and surgical treatment: A systematic review and meta-analysis

Abstract: Background: Ectopic pregnancy (EP), one of the most common gynecological emergencies, is the major cause of maternal death in the first trimester and increases the incidence of infertility and repeat ectopic pregnancy (REP). The aim of this study was to compare the effects of different treatment methods for tubal EP on natural pregnancy outcomes.Methods: We systematically searched PubMed, Embase, Cochrane Library, Web of Science, and Clinical Trials for observational studies on EP (published until October 30,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Similarly, in a retrospective cohort of 30,450 PID patients and 91,350 controls, Huang et al found that PID patients had a 2.121-fold (p = 0.003) higher risk of developing an ectopic pregnancy in Taiwan region [10]. All these results are supported by Xia et al who explored the relationship between chlamydia trachomatis infections and ectopic pregnancy in a recent meta-analysis and systematic review, and found that the association between chlamydia trachomatis infections and the risk of EP showed an odds ratio (OR) of 3.03, with a 95% confidence interval (CI) of 2.37 to 3.89 [11]. Our result is therefore in line with numerous studies that have identified PID as a major risk factor for EP, due to scarring leading to tubal obstruction that interferes with egg capture and migration.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, in a retrospective cohort of 30,450 PID patients and 91,350 controls, Huang et al found that PID patients had a 2.121-fold (p = 0.003) higher risk of developing an ectopic pregnancy in Taiwan region [10]. All these results are supported by Xia et al who explored the relationship between chlamydia trachomatis infections and ectopic pregnancy in a recent meta-analysis and systematic review, and found that the association between chlamydia trachomatis infections and the risk of EP showed an odds ratio (OR) of 3.03, with a 95% confidence interval (CI) of 2.37 to 3.89 [11]. Our result is therefore in line with numerous studies that have identified PID as a major risk factor for EP, due to scarring leading to tubal obstruction that interferes with egg capture and migration.…”
Section: Discussionmentioning
confidence: 62%
“…Hao et al showed that there was no significant difference in the odds of subsequent intrauterine pregnancy and repeat ectopic pregnancy following treatment with MTX compared to salpingostomy. [8] However, no studies have shown the effect of tubal patency on a second pregnancy. The condition of the fallopian tube after tubal pregnancy treatment, whether it is unobstructed or not, has a significant impact on future pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al showed that there was no significant difference in the odds of subsequent intrauterine pregnancy and repeat ectopic pregnancy following treatment with MTX compared to salpingostomy. [8] However, no studies have shown the effect of tubal patency on a second pregnancy.…”
Section: Discussionmentioning
confidence: 99%